Leaf Anatomy of Xylopia aromatica (Lam.) Mart. (Annonaceae) occurring in a rocky savannah in the Brazilian Amazonian (Acta Scientiarum. Biological Sciences, 2018)
Savannas of the Amazon Region of Mato Grosso State have an unique  ecological identity due to the complexity of the Cerrado-Amazon transition region, their geographical isolation and the physical-chemical properties of the soil. This study aimed to characterize the leaf anatomy of Xylopia aromatica, and to identify potential adaptive traits to the xeric environment. We collected adult leaves from X. aromatica from a Amazonian savannah located in the Nova Canãa do Norte city, Mato Grosso. The leaves were fixed and stored in 70% ethanol. Cross sections were obtained by free hand with the aid of a razor blade, stained with astra blue and basic fuchsin, and mounted on histological slides. Characters considered adaptive: thick cuticle, epidermal cells with thickened walls, the presence of silica in the epidermis, trichomes, hypostomatic leaves, stomata on the same level as the other epidermal cells, presence of hypodermis, and dorsiventral mesophyll with palisade parenchyma occupying more than 50%. The anatomical characters presented are of great importance for the establishment and development of X. aromatica in xeric environments. They contribute to the protection of the leaves from many biotic and abiotic factors to which they are subjected, thus ensuring the species survival in the savannic environment.